EP 132. Motivational characteristics of expert performance. Issue 9 (September 2016) - Neumann, N.; Lotze, M.
Abstract : Objective: Expert performance is characterized by the consistent performance at a superior level in a cognitive, artistic, motor or other domain (Ericsson and Lehmann, 1996 ). The objective of the current study was to highlight motivational factors that enable the persistent training that is a necessary precondition for expert performance in any domain. Therefore we compared fMRI-activation in experts with those of naïve participants during task performance in the field of expertise (finger sequence encoding for pianists, creative writing for writers and portrait drawing for students of fine arts). We hypothesized expert-specific activation of motivational structures in these tasks. Methods: We reanalysed fMRI data collected in studies with expert groups of music, creative writing, and drawing (Erhard et al., 2014; Pau et al., 2013 ; Neumann et al, in preparation ). Data were acquired using a 3.0 Tesla Siemens MAGNETOM Verio MRI scanner (Erlangen, Germany) with a 32-channel head coil. Echo-Planar-Imaging (EPI) with a repetition time (TR) of 2000 ms for the whole brain volume was measured together with a T1-weighted high-resolution anatomical image. Region of interest analyses comprised the ventral and dorsal striatum, amygdalae and hippocampi, ventromedial and ventrolateral prefrontal cortices, anterior insulae, ventral tegmentum and periaqueductal grey. Results are reported as FWE-corrected values with p  < 0.05 per ROI. Results: All texts and portraits produced by the experts were superior as rated by specialists ( t  > 3.3; p  < 0.01). Accordingly, later finger sequence encoding was superior in pianists compared to controls ( t  = 2.60; p  < 0.05). Functional imaging revealed that artists compared to controls showed increased fMRI activation in left ventral pallidum ( t  = 3.07: pFWE = 0.05; MNI-coordinates: −27, −15, −3) and left ventral tegmentum ( t  = 3.72; pFWE = 0.03; MNI-coordinates: −16, −10, −12) during the exact drawing of a portrait, and increased left hippocampal activation during sketchy drawing ( t  = 3.83: pFWE = 0.027; MNI-coordinates: −39, −18, −15). Pianists showed increased left putamen ( t  = 4.54: p FWE = 0.004; MNI-coordinates: −30, 12, 9), anterior insula ( t  = 3.64: p FWE = 0.025; MNI-coordinates: 39, 3, 6) and periaqueductal grey ( t  = 3.76: p FWE = 0.016; MNI-coordinates:−9, −27, 21) activation. For creative writers, we found an increase of activation in the left caudate ( t  = 3.91: p FWE = 0.025; MNI-coordinates: −9, 3, 15). Conclusion: Basal ganglia activation of the dominant hemisphere is a common characteristic of the three expert groups investigated across different functional imaging designs. However, the exact localization of increased basal ganglia recruitment differed largely in the three expert groups in comparison to control participants. Whereas drawing experts showed increased activation in the ventral pallidum receiving dopaminergic inputs from the ventral tegmental area, pianists activated motor training associated parts of the putamen, and in expert writers more cognitive aspects seemed to be recruited (Alexander et al., 1986 ).